Incidence Rate of Myocardial Infarction in HIVâ€“Infected Individuals: A System-atic Review and Metaâ€“Analysis - Gersom, Camoya; Thirza, Savannah Quila (Bioinformatics and Biomedical Research Journal, 2018)
Background: The incidence rate of myocardial infarction has been reportedly higher in human immunodeficiency virus (HIV)â€“infected individuals compared to in uninfected individuals. HIV infection is suggested to have increased the risk of myocardial infarction (MI). To review the incidence rate of myocardial infarction in HIVâ€“infected individuals compared to in uninfected individuals in its relation to HIV infection as a potential risk factor of MI incident. A literature search was performed in Google Scholar, PubMed, and Cochrane databases with keywords â€œHIV risk myocardial infarctionâ€ and â€œmyocardial infarction in HIVâ€ ranging from 2013 to 2019. Inclusion criteria wasfull-text observational studies that reported the incidence rate of myocardial infarction in HIVâ€“infected individuals compared to in uninfected individuals. A total of 6 studies were eligible for review. We performed the metaâ€“analysis with Review Manager 5.3 in May 2019. We reviewed several studies that discussed the association between HIV infection and myocardial infarction. The incidence rate of MI is higher in HIVâ€“infected individuals compared to in nonâ€“infected individuals. It is suggested that Framingham Risk Score does not directly contribute to the higher incidence of MI in patients with HIV. Several studies also reported that low CD4 cell count and HIVâ€“1 RNA levels less than 500 copies/mL contribute directly to the risk of myocardial infarction. There is a higher incidence rate of myocardial infarction among HIVâ€“infected individuals compared to among nonâ€“infected individuals. Several suggested factors include low CD4 cell count and HIVâ€“1 RNA levels less than 500 copies/mL. Thus, it may be suggested that HIV infection is a potential risk factor of MI. Further studies are needed to better understand the mechanism of HIV infection as a risk factor of MI incident.